Psychometric adaptation of the reduced version of Driving Anger Scale in a Spanish sample. Differences by age and gender - Herrero Fernández, David (Anales de Psicología / Annals of Psychology, 2011)
The present study examined the events that provoke driving anger in a sample of Spanish drivers. With this aim, the 14-item short version of the Driving Anger Scale (Deffenbacheret al., 1994) was applied to a sample of 528 drivers. Exploratory and confirmatory factor analysis showed a good fit of three factors, which were called Impeded Progress by Others ( = .77), Reckless Driving ( = .66) and Direct Hostility ( = .87). These factors can be summed to obtain a global score ( = .84). Additional analyses showed that there was not significant interaction effect between age and gender in anger neither significant effect by gender. However, younger drivers scored higher than older in all the factors: Impeded Progress by Others (η2 = .03), Reckless Driving (η2 = .02), Direct Hostility (η2 = .04) and Global Score (η2 = .04).